(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper presents a model of preventing smuggling of valuable trees like sandal trees, red sandal trees in the forest area. In proposed system in order to detect cutting down of valuable trees immediately, we use vibration sensors and continuity sensors. Here vibration sensor is used to sense the vibration created during cutting down the tree and continuity sensor is used to check the continuity between neighbouring trees. In existing system, RFID is used to identify the missing tags in the tree. This system proposes an intelligent system to track the detection of illegal smuggling of trees in forest. Existing system makes use of various technologies such as RFID, Wifi etc,. RFID based systems lack in rain if passive taxes are used or lack in cost effectiveness. Similarly, wifi based systems becomes costlier and require constant network connection. Hence this project proposes a wifi based tracking system. The stationary wifi transceiver consists of ESP8266 with Arduino Uno development board which detects the mobile transceiver. The mobile transceiver detects mobile transceivers under its vicinity and sends the data to other stationary transceiver and ultimately the data stored in data base